Adolescent Stimulation of D2 Receptors Alters the Maturation of Dopamine-dependent Goal-Directed Behavior - Naneix, Fabien (Nature Publishing Group, 2013)
Adolescence is a period of high sensitivity to drugs and rewards, characterized by the immaturity of decision-making abilities. A chronic stimulation of reward systems during this period might constitute a factor of vulnerability to the development of psychiatric disorders. However, the long-term consequences of such an exposure have seldom been explored. Here, we investigate at the adult age the effects of chronic dopamine (DA) stimulation during adolescence on both the maturation of DA systems and the cognitive processes underlying goal-directed actions. We first demonstrate that chronic stimulation of D2 receptors by quinpirole during adolescence alters the development of DA systems. This treatment has particularly prominent effects on the mesocortical DA pathway where it decreases DA fibers density, DA concentration, and DA receptors expression. Furthermore, we show that quinpirole-treated rats exhibit specific impairments in instrumental goal-directed behavior, as they fail to adapt their action when action–outcome relationships change in a contingency degradation procedure. These results therefore highlight the vulnerability of DA system and prefrontal areas to prolonged stimulation during adolescence, and its potential long-term impact on cognitive functions.